Temporal Optimization of Sowing Windows for Enhancing Off-Season Soybean Seed Yield: Evidence from Two-Year and Pooled Data - Priyanka M (The Indian Journal of Agricultural Sciences, 2026)
The experiment was conducted during the years 2022–23 and 2023–24 at the Seed Unit, Raichur, to identify the optimal sowing window for off-season seed production of soybean. The study was laid out in a split-plot design with three replications, comprising two varieties (JS 335 and DSB 21) and six sowing dates. Results revealed that sowing during the first fortnight of November (D1) consistently recorded superior performance in both years and pooled analysis. This treatment significantly improved key phenological parameters, including longer duration from planting to R1, extended reproductive phase (R1 to R8), and higher days to 50% flowering in both varieties. The favorable growth period under D1 contributed to better crop development and efficient resource utilization. Consequently, the highest seed yield per plot was also recorded under this sowing window, with JS 335 outperforming DSB 21. The improved performance under early November sowing may be attributed to optimum temperature and photoperiod conditions during critical growth stages. It can be concluded that sowing soybean during the first fortnight of November is the most suitable window for off-season seed production in the North Eastern Dry Zone of Karnataka, ensuring better growth and higher seed yield.